Profil Pasien Inflammatory Bowel Disease di RSUP Prof. Dr. R. D. Kandou Manado Periode Tahun 2020 - 2022 - Damiyanti, Ni Nyoman E.; Waleleng, Bradley J.; Umboh, Octavianus R. H. (e-CliniC, 2025)
Abstract: Inflammatory bowel disease (IBD) is a chronic idiopathic inflammation occurring in the digestive tract, divided into two types, namely ulcerative colitis (UC) and Crohn's disease (CD). This study aimed to obtain the profile of inflammatory bowel disease patients based on gender, age, and the most common clinical manifestations at the Gastroenterology Division of the Department of Internal Medicine, Prof. Dr. R. D. Kandou Manado Hospital from January 1, 2020, to December 31, 2022. This was a retrospective descriptive study using patients’ medical records from 2020 to 2022. The results showed that there were 86 IBD patients, with 49 CD cases and 37 UC cases; males (n=54) and females (n=32); age>45 years (65.1%), age 25-45 years (26.7%), and age<25 years (8.1%). Clinical presentations included abdominal pain, epigastric pain, liquid stools, weakness, and bloody stools. In conclusion, patients with inflammatory bowel disease were more prevalent in Chron disease than ulcerative colitis. Males were more common than females and the majority were over 45 years old. The most common clinical manifestation was abdominal pain. Keywords: inflammatory bowel disease; Crohn's disease; ulcerative colitis Abstrak: Penyakit radang usus merupakan radang idiopatik kronis yang terjadi pada saluran pencernaan yang dibagi atas dua jenis yaitu kolitis ulseratif (KU) dan penyakit Crohn (PC). Penelitian ini bertujuan untuk mengetahui gambaran pasien radang usus berdasarkan jenis kelamin, usia, dan gambaran klinis tersering di Divisi Gastroenterologi Ilmu Penyakit Dalam RSUP Prof. Dr. R. D. Kandou Manado periode 1 Januari 2020 - 31 Desember 2022. Jenis penelitian ialah deskriptif retrospektif menggunakan data sekunder pasien selama periode tahun 2020 - 2022. Hasil penelitian mendapatkan jumlah pasien radang usus (n=86), PC (n=49), dan KU (n=37); laki-laki (n=54) dan perempuan (n=32); usia >45 tahun (65,1%), usia 25-45 tahun (26,7%), dan usia <25 tahun (8,1%). Gambaran klinis nyeri perut, nyeri ulu hati, BAB cair, lemah badan, dan BAB darah. Simpulan penelitian ini ialah pasien radang usus lebih banyak terdapat pada penyakit Crohn daripada kolitis ulserosa, didominasi oleh laki-laki dan usia >45 tahun. Gambaran klinis yang paling sering ditemukan ialah nyeri perut. Kata kunci: penyakit radang usus; kolitis ulseratif; penyakit Crohn